Effect of Pingyanghuangtang tea on hyperuricemia in mice and its mechanism - LOU Zhenyou; ZHOU Yongjun; ZHONG Weibiao; CHEN Yunyang; TU Youying; LIU Junsheng; HE Puming (浙江大学学报. 农业与生命科学版, 2024)
Hyperuricemia can cause serious harm to the human body, and its incidence has been increasing in recent years. In this study, Pingyanghuangtang tea was used to investigate the effects of different dosages of Pingyanghuangtang tea liquor on serum uric acid levels in hyperuricemic mice and its mechanism. The results showed that different dosages of Pingyanghuangtang tea liquor could reduce the serum uric acid levels in hyperuricemic mice, but there were no significant differences between the different dosages. Through the analysis of uric acid production and decomposition pathways, it was found that different dosages of Pingyanghuangtang tea liquor could significantly inhibit the activity of xanthine oxidase in the liver, thereby reducing the production of uric acid. Additionally, Pingyanghuangtang effectively improved the pathological characteristics of the glomerulus and renal tubules in hyperuricemic mice. It also showed that Pingyanghuangtang modulated the composition and structure of the gut microbiota in hyperuricemic mice. It was speculated that Pingyanghuangtang could promote uric acid excretion by protecting the kidney and modulating the gut microbiota of hyperuricemic mice, thereby reducing the serum uric acid level. This study provides some reference for the efficacy research and product development of yellow tea and the prevention and treatment of hyperuricemia.